1985
DOI: 10.1136/bmj.291.6489.163
|View full text |Cite
|
Sign up to set email alerts
|

Increase of oleic acid in erythrocytes associated with malignancies.

Abstract: Total lipid extracts of erythrocyte cell membranes from 60 patients with documented malignancies, 41 patients with various acute and chronic diseases, and 40 healthy subjects were analysed. The results were expressed as ratios of stearic to oleic acid, reflecting the diegree of desaturation of stearic acid. The mean ratios for the healthy subjects and controls without cancer were 1-5 (SD 0 27) and 1 45 (0 28), respectively, whereas the ratios for patients with malignancies were consistently lower than the cut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
2

Year Published

1986
1986
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 9 publications
2
29
2
Order By: Relevance
“…A reduction of stearic to oleic acid ratio in the platelets of patients with active malignancies (Copland et al, 1990) has previously been reported. Similar findings were observed in the peripheral blood cells of patients with chronic leukaemia (Apostolov et al, 1985) and in the circulating erythrocytes of patients with solid tumours (Wood et al, 1985). The reason for the decreased stearic to oleic acid ratio in malignant tissue is not clear at present.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A reduction of stearic to oleic acid ratio in the platelets of patients with active malignancies (Copland et al, 1990) has previously been reported. Similar findings were observed in the peripheral blood cells of patients with chronic leukaemia (Apostolov et al, 1985) and in the circulating erythrocytes of patients with solid tumours (Wood et al, 1985). The reason for the decreased stearic to oleic acid ratio in malignant tissue is not clear at present.…”
Section: Discussionsupporting
confidence: 69%
“…It has been suggested that this reduced ratio in erythrocytes is a useful diagnostic marker for malignancies (Wood et al, 1985). However, a similar decrease in stearic:oleic acid ratio has been observed in cells infected with Coxsackie and Herpes simplex type 2 viruses (Nozawa et al, 1982) and in patients with non-malignant diseases (Copland et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It should be stated however, that elevated lipid levels may not be the result of dietary influences but may reflect some underlying metabolic disturbance associated directly with the disease or with some hormonal factor related to the disease. A recent study of membrane fatty acid composition in red cells obtained from patients with different types of cancer, including breast cancer, showed major differences in fatty acid profiles in the cancer group (Wood et al, 1985). It was suggested that such differences may reflect a fundamental defect in lipid metabolism associated with certain types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid changes in malignancy Wood et al (1985) found increased desaturation of stearic (18:0) to oleic acid (18:1) in red cell membranes from patients with colorectal cancer, and a consequently decreased 18:0/18:1 ratio. We found a similar change in the plasma 18:0/18:1 ratio in the tumour-bearing mice, but the reverse in the liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of saturation affects membrane fluidity and permeability (Schlager & Ohanian, 1980a); 18:0/18:1 is lower in red cell membranes from cancer patients (Wood et al, 1985); the latter ratio and 16:0/16:1 indicate delta-9-desaturase activity; the 18:2/20:4 ratio reflects delta-6-denaturase, elongase and delta-5-desaturase activities and eicosanoid production (Fulton, 1984;Hubbard et al, 1988); 20:3/20:4 reflects delta-5-desaturase activity; the n-6/n-3 ratio indicates tumour aggressiveness which is high when n-6 levels are low (Lanson et al, 1990). …”
mentioning
confidence: 99%